Characteristics of Sports Injuries in Those Who Train for Police or Military Personnel Physical Proficiency Test - Lima, Yavuz (Cerrahpaşa Medical Journal, 2023)
Objective: The purpose of this study was to evaluate the characteristics of injuries in those who train for the police or military personnel physical proficiency test. Methods: All participants who applied to Balıkesir Atatürk City Hospital Sports Medicine Unit with injuries that occurred in police or military personnel proficiency tests between January 1, 2021, and January 1, 2022, were evaluated, and the mechanism, location, type, and severity of injuries were recorded. Results: A total of 78 participants (age 23.5 ± 3.2) were evaluated during the study period. While 61.5% of injuries (n = 48) were overuse injuries, the most common injury type was bone stress injury (37.2%, n = 29), the most common injury location was leg (30.8%, n = 24), and 51.3% of injuries (n = 40) were severe. The most common injury locations were knee and leg for males and hip/groin for females (P < .01, effect size = 0.41). Conclusion: Musculoskeletal complaints, in particular, in the lower extremities in those who train for the physical proficiency tests should be evaluated in detail, and professional health support should be provided when they get injured. Cite this article as: Lima Y. Characteristics of sports injuries in those who train for police or military personnel physical proficiency test. Cerrahpaşa Med J. 2023;47(1):68-71.